The effect of capital structure, sales growth, working capital turnover, and liquidity on company profitability with firm size as a moderating variable - Dianti, Prima Mei; Bawono, Andy Dwi Bayu (Enrichment : Journal of Management, 2024)
This study examines the effects of capital structure, sales growth, working capital turnover, and liquidity on profitability, with firm size as a moderating variable. Using financial data from food and beverage companies listed on the IDX (2019–2023), profitability is measured by ROA, while independent variables include DER, sales growth, working capital turnover, and CR. Firm size is represented by the natural logarithm of total assets. Data analysis through SPSS applies multiple and moderation regression. Results indicate that capital structure and sales growth do not significantly influence profitability, while working capital turnover does. Firm size moderates the effects of capital structure and sales growth on profitability but does not moderate the impacts of working capital turnover or liquidity. The study's limitations include the use of limited financial ratios, reliance on reports in Rupiah, and a narrow industry focus. Future research may expand by incorporating additional financial metrics, utilizing foreign currencies, and covering a wider sample from diverse sectors to better capture broader economic trends.